2006
DOI: 10.4049/jimmunol.177.4.2276
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Induction of CD4+ T Cell Responses through In Vivo Targeting of Antigen to Dendritic Cell-Associated C-Type Lectin-1

Abstract: Targeting of Ags and therapeutics to dendritic cells (DCs) has immense potential for immunotherapy and vaccination. Because DCs are heterogeneous, optimal targeting strategies will require knowledge about functional specialization among DC subpopulations and identification of molecules for targeting appropriate DCs. We characterized the expression of a fungal recognition receptor, DC-associated C-type lectin-1 (Dectin-1), on mouse DC subpopulations and investigated the ability of an anti-Dectin-1 Ab to deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
156
2

Year Published

2007
2007
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 51 publications
(59 reference statements)
5
156
2
Order By: Relevance
“…In contrast, more recent studies suggested preferential expression by CD8 -DC [34,39]. Although we did not detect strong dectin-1 expression by the DC subsets, approximately 25-35% of both CD8 + and CD8 -DC expressed dectin-1 and similar percentages of both DC subsets phagocytosed yeasts in a short-term assay.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, more recent studies suggested preferential expression by CD8 -DC [34,39]. Although we did not detect strong dectin-1 expression by the DC subsets, approximately 25-35% of both CD8 + and CD8 -DC expressed dectin-1 and similar percentages of both DC subsets phagocytosed yeasts in a short-term assay.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas neutrophils and macrophages show heterogeneous but strong expression of dectin-1 [16,38], dectin-1 expression on DC subsets is not well defined. Initially, subpopulations of both CD8 + and CD8 -DC were described to express dectin-1 [38], whereas others detected dectin-1 only on a fraction of CD8 -DC [39]. We observed low staining with antidectin-1 antibody on both DC subsets and both CD8 -and CD8 + DC contained comparable numbers of dectin-1-positive cells ( Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Dectin-1 can also signal to regulate innate immune responses through activation of the Syk tyrosine kinase and subsequent production of interleukin (IL)-2 and IL-10 ( Rogers et al, 2005). In the mouse, Dectin-1 is expressed by CD8a À CD11b þ DCs in spleen, lymph nodes and in skin (dermal DCs) and a recent study by Carter et al (2006b) has shown efficient induction of both T cell (CD4 and CD8) and antibody responses by antigen delivered with a Dectin-1-targeting antibody. They also compared responses to Dectin-targeted antigen with those triggered with a DEC-205-targeting antibody, that targets CD8a þ CD11b À DCs and found qualitatively different outcomes.…”
Section: Antibody-targeted Vaccines T Keler Et Almentioning
confidence: 99%
“…Indeed, targeting Ags to the CD8␣ ϩ subset using Ab against the C-type lectin receptor DEC205 (4 -7) elicit potent Ag-specific cytotoxic responses in vivo. In contrast, targeting lectins expressed on the CD8␣ Ϫ subset of conventional DCs induce Ab responses but poor cellular-mediated responses (8,9). Whether the relative ability to display peptides on class I or II products is mainly cell type or receptor regulated, however, requires further studies (10).…”
Section: Selection Of An Antibody Library Identifies a Pathway Tomentioning
confidence: 99%